Parathyroid hormone intermittent administration promotes delay on rat incisor eruption. (September 2016) - Silva, M.A.D.; Vasconcelos, D.F.P.; Marques, M.R.; Barros, S.P.
Highlights: PTH (1–34) intermittent administration accelerated alveolar bone formation. PTH (1–34) intermittent administration delayed the eruptive process. PTH (1–34) administration increased in the area density of Sharpey fibers. Abstract: Objective: This study evaluated the influence of parathyroid hormone (PTH) (1–34) intermittent administration on rat eruption rates of lower incisors under normo, hyper and hypofunctional conditions, Sharpey fibers insertion, and alveolar bone formation. Materials and methods: Wistar male rats received PTH (1–34) three times a week during the entire experimental period, 31 days. Control animals received the same concentration of the vehicle solution during the same period. Three injections of alizarin were also performed. The experiment evaluated the eruptive rate, the alveolar bone formation and also the morphology, and the area density of Sharpey fibers. After the sacrifice, the mandibles were dissected and samples were prepared for fluorescence and scanning electron microscopy observations. Results: PTH-treated animals showed significantly reduced eruption rates in all different functional conditions. Analysis evidenced that PTH-treated rats present an increase in bone formation and area density of the Sharpey fibers. Conclusion: We concluded that the PTH (1–34) intermittent administration reduced the eruptive process rates, through bone formation enhancement and increase in the area density of Sharpey fibers.